IMPLEMENTASI SENSOR KELEMBAPAN DAN PH TANAH UNTUK OPTIMALISASI PERTUMBUMBUHAN TANAMAN SELEDRI - Dedy Harto; Kharis Hudaiby Hanif; Farhan Muhammad Nabil (Elektrika Borneo, 2026)
Soil moisture and pH are important factors that influence the growth of celery (Apium graveolens). Manual monitoring of soil conditions is often ineffective because it cannot provide real-time soil condition information. This study aims to implement a sensor-based soil moisture and pH monitoring system to support the optimization of celery plant growth. The developed system uses a YL-96 soil moisture sensor and a soil pH sensor integrated with a microcontroller to measure and monitor soil conditions. Based on testing of 10 field data samples, the system is able to identify the "Moist and Normal" status with a high success rate. Data analysis shows the system has an accuracy of 90%, with only 10% of errors (1 in 10 data points) caused by fluctuations in sensor readings. The results show that the developed system is able to monitor soil conditions in real-time so that it can be used as an aid in managing planting media to improve celery plant growth.